THE SPECIATION OF WATER IN HAPLOGRANITIC GLASSES AND MELTS DETERMINED BY IN SITU NEAR-INFRARED SPECTROSCOPY - Nowak M.; Behrens H. (My University, 1995)
First measurements of water species in an aluminosilicate melt of haplogranitic composition at temperatures up to 800°C and at a pressure of 1500 bar determined by in situ near-infrared spectroscopy are presented. These measurements clearly show that both water molecules and hydroxyl groups are stable species in the melt. The concentration of hydroxyl groups in the melt varies strongly with temperature and is considerably higher than predicted by previous spectroscopic studies on glasses at room temperature. Changes of hydroxyl group concentration with temperature were also observed for the glassy state and are attributed to a local reaction between water molecules and bridging oxygens resulting in the formation of hydroxyl group pairs. For the studied composition with a total water content of 4.14 wt% we found contents of water present as hydroxyl groups of 1.46 wt% at 25°C, 1.61 wt% at 250°C (in the glass), and 3.23 wt% at 800°C (in the melt). Assuming an ideal behaviour of the oxygen-bearing species in the reaction, standard state enthalpies of 33.6 +/- 2.0 kJ.mol-1 (melt) and 1.52 +/- 0.20 kJ.mol-1 (glass), and standard state entropies of 29.8 +/- 1.2 J.mol-1.K-1 (melt) and -18.6 +/- 0.4 J.mol-1.K-1 (glass) were determined for the reaction (H2O + O = 2 OH).